SMART WALKING STICK FOR VISUALLY IMPAIRED PEOPLE - Azmi, Faezuan (Journal of Computing Technologies and Creative Content, 2019)
The white cane, due to its primitive design, is unable to offer the blind and visually impaired a level of independence that is achievable with modern technology. The Smart Walking Stick looks to upgrade the white cane by increasing security and usability of the cane while ensuring an affordable price for an older and lower income demographic. This was done by including an ultrasonic sensor to detect potential obstacles at an extended distance from the user, vibrating motors to alert the user of these obstacles via haptic feedback, and comfortable handle in order to increase the comfort and ease of the cane. Observations and basic testing confirm the effectiveness of the vibrations in the handle and the accuracy of the ultrasonic sensor up to 1.5 meters past the tip of the cane.